(untitled) (European Journal of Formal Sciences and Engineering, 2022)
The use of membranes for gas upgrading has increasingly become of interest as it has shown great potential for efficient and affective gas purification and a pathway to green energy. The emission of greenhouse gases to the atmosphere has detrimental effects on the economy in terms of global warming which has led to many natural disasters, heat waves, food shortage, loss of life and property. To combat this, studies of capturing and utilizing greenhouse gases are ongoing. In this paper, the study of biogas components (methane and carbon dioxide) diffusion through membranes are studied to employ its use as a solution for the challenge. The study involved the use of membranes of different pore sizes (15, 200 and 6000nm) to ascertain the flow characteristics and regime of the gases under different operating conditions. Single gas permeation tests were conducted, and the results show the flow of gases is dependent on factors including molecular weight, kinematic diameter and viscosity of the gas components. It was observed that pressure has a greater influence on the gas flow through membranes compared to temperature with the effect of pore size having the greatest impact. The flux of methane through the membrane is greater than that of carbon dioxide in regular pore geometry and depicts a greater potential for upgrading of biogas.